Limits of Visual Detection for Finasteride Polymorphs in Prepared Binary Mixtures: Analysis by X-ray Powder Diffraction - Bezzon, Vinicius D. N. [UNESP]; Antonio, Selma G. [UNESP]; Paiva-Santos, Carlos O. [UNESP] (Wiley-Blackwell, 2014)
Finasteride (FNT) is a drug that inhibits human enzyme type II 5-reductase that metabolizes testosterone into dihydrotestosterone. There are two enantiotropic polymorphs with known crystal structure: designated as forms I and II. Identification and control of these polymorphic forms in mixtures can be performed using X-ray powder diffraction (XRPD) data and Rietveld method (RM). As experimental conditions may limit the detection of minority phases in mixtures, it is interesting to show what are these limits for some usual and one high-resolution equipment. So, in this work, we discuss the parameters to find the limit of the detection in binary mixtures of forms I and II of FNT according to each experimental condition. The samples analyzed were binary mixtures prepared with anhydrous polymorphs of the drug FNT. These samples were measured in four diffractometers with different experimental condition. These equipments represent the main resolutions generally used for drug analysis by XRPD. For the development of this work, a batch of form I was obtained pure, and another batch with forms I and II was used to obtain pure form II by heat treatment. Depending on the experimental condition, the polymorphs could be detected in a proportion as low as 0.5 wt%. (c) 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:3567-3575, 2014
Keywords: X-ray powder diffractometry; crystal structure; crystallinity; polymorphism; quantitative phase analysis; transition; finasteride; Rietveld method; limits of visual detection